2006
DOI: 10.1189/jlb.0406262
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RAGE induces elevated O2− generation by mononuclear phagocytes in diabetes

Abstract: Oxidative stress has been found to play a role in the pathogenesis of diabetic complications. The aim of this study was to define the oxidative burst of diabetic monocytes to characterize the phenotype associated with poor diabetic control. Superoxide (O 2 -) is the first molecule generated during the respiratory burst of phagocytes by NADPH oxidase, and its generation by monocytes from 26 controls and 34 diabetic subjects was evaluated in this study. Under resting states or stimulation by PMA or opsonized zym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…Because it is difficult to standardize the individual variations among human subjects with respect to monocyte/macrophage functions, we used THP-1 cells to study the mechanism of hyperglycemia-induced changes in PKC activation and involvement of pleckstrin in vitro. Preliminary experiments by our group and others confirm the expression of RAGE on THP-1 cells as well as functions such as oxidative burst and cytokine production (41,46). Furthermore, a similar phosphorylation pattern of PKC substrates responding to PMA stimulation between THP-1 cells and human monocytes (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Because it is difficult to standardize the individual variations among human subjects with respect to monocyte/macrophage functions, we used THP-1 cells to study the mechanism of hyperglycemia-induced changes in PKC activation and involvement of pleckstrin in vitro. Preliminary experiments by our group and others confirm the expression of RAGE on THP-1 cells as well as functions such as oxidative burst and cytokine production (41,46). Furthermore, a similar phosphorylation pattern of PKC substrates responding to PMA stimulation between THP-1 cells and human monocytes (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…AGE are nonenzymatically glycated molecules that are elevated in the serum of diabetics (46,52). Many cell types express RAGE (53) and it has be demonstrated that binding of AGE to innate immune cells leads to increased inflammation (54 -56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement of RAGE by its ligands generates ROS, in part via superoxide-producing enzyme NADPH oxidase and also, possibly, via mitochondrial pathways in both vascular and neuronal cells affected by diabetes (8)(9)(10). The source of the ROS in ß-cells also remains controversial with two proposed candidates, i.e., leakage from the mitochondrial electron transport chain and NADPH oxidase (30).…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions, especially in diabetic vascular diseases, RAGE expression is often upregulated with increased expression of its ligands as well (6,7). Engagement of RAGE by its ligands was shown to generate reactive oxygen species (ROS) via receptor-dependent signaling and to activate inflammatory signaling cascades in vascular and inflammatory cells (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%